To Compare the Effect of Ischemic Compression versus Dynamic Stretching Exercises on Pain in Subjects with Upper Trapezitis. - Poornashree M.; Kamalakannan M.; Anitha A.; Ramana K. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: The most prevalent musculoskeletal ailment is trapezitis, which primarily affects the upper trapezius muscle due to overuse or strain. Purpose: The purpose of this study is to find out the effect of ischemic compression and dynamic stretching exercises on pain in subjects with upper trapezitis. Materials and Methods: A total of 40 subjects were chosen from Neha Clinic and assigned to two groups, namely the ischemic compression group along with Transcutaneous Electrical Nerve Stimulation (TENS) (n=20) and the dynamic stretching exercises group along with TENS (n=20), based on inclusion and exclusion criteria. Visual analog scale (VAS) and cervical range of motion (CROM) were used as outcome measures. The entire process was performed from November 2022 to April 2023. Result: The mean value of ischemic compression at the post-test was found to be higher than the mean value of dynamic stretching exercises, with a p-value of less than 0.0001 Conclusion: The findings of this study suggest that ischemic compression is more effective than dynamic stretching exercises in reducing pain associated with upper trapezitis.